How to be the Best Influencer: The Impact of Personality, Audience Perceptions, and Narcissism on Social Media Influencing - Saroya, Japkaran (MacEwan University Student eJournal, 2024)
Social media influencers (influencers) are individuals who have built followings on social media platforms by sharing content with their audience and can be paid to do so through promotional posts and partnerships with brands and businesses. Social media influencing has grown into a lucrative career for people worldwide. But which factors are essential to optimize your social media growth online? This paper reviews how specific personality characteristics, audience perceptions, and narcissism play a role in the success of social media influencers and how to utilize social media to create success in social media influencing.